Preparation of 3D nanostructured porous graphene framework for oil sorbent application - Tarmizi Pohan, Nurul Aqilah Pohan (2021)
The preparation of graphene in three-dimensional (3D) mode serves as an alternative to maintain its characteristically large surface area, which under normal circumstances, is diminished by the restacking of the individual graphene sheets. In addition, 3D graphene enables the surface area to be reserved and combined with void spaces, the potential as an oil absorbent material is anticipated. In this study, 3D graphene oxide (3D GO) was prepared f rom the Pickering emulsion of GO in water/toluene mixture. The Pickering emulsion was f irst prepared by mixing toluene (9.35 M) and water in the presence of graphene oxide (2 mg mL-1). The trapped solvents were then removed by f reeze-drying thus forming porous structure. At PVA content 30%, 120 minutes of sonication and thermal reduction temperature of 150 °C for 30 minutes, the targeted surface area improvement was observed where the surface area of 3D GO obtained is 104 m2 g-1 compared to the surface area of GO in 2D form which is 36 m2 g-1. Oil absorption capacity obtained is 145 g g-1 which is on par with other graphenebased oil absorbent. As conf irmed by scanning electron microscopy (SEM), mercury intrusion porosimetry (MIP) and Brunauer-Emmett-Teller (BET), the 3D GO displayed dual pore size distributions of macropores and mesopores where porosity value of 0.95 obtained f rom bulk density of 0.03 g mL-1 ratio to particle density of 0.60 g mL-1. The reusability study meanwhile shows at capacity of 145 g g-1 to 55 g g-1 ten repetition sorption-desorption cycle, the 3D GO able to be reuse although downfall significantly.